Estimation of embryotoxic and teratogenic effects of ivermectin in laboratory animals - N. B. Yemelyanova; N. A. Samoylovskaya (Российский паразитологический журнал)
Injection of ivermectin in a dose of 0,2 mg/kg to pregnant rates in critical stage of embryogenesis at days 1-6, 7-14 and 15-19 did not effect animals’ beha- vior. Duration of pregnancy in laboratory female rats was at control and normal physiological level for present kind of animas. Delivery process was normal with- out clinical features and complications. Presence of milk in rats’ stomachs allows to conclude that the injection of tested medicine to female rats did not affect their lactation and sucking reflex. At injection of ivermectin in a therapeutic dose at days 1-6, 7-14 and 15-19 of pregnancy the value of rats' death in the first life month was compatible with control values. According to our observation there was no effect of ivermectin on postnatal development in rats in form of death and external malformations. All rats were born healthy, responded well to external stimuli, had a good appetite and pursued an active life. Results of laboratory research allow to conclude that ivermectin injection to rats in a therapeutic dose of 0,2 mg/kg in dif- ferent pregnancy terms including critical stages doesn't have embryotoxic and tera- togenic effects